Willow (Salix spp.) bark hot water extracts inhibit both enveloped and non-enveloped viruses: study on its anti-coronavirus and anti-enterovirus activities - Reshamwala, Dhanik; Shroff, Sailee; Liimatainen, Jaana; Tienaho, Jenni; Laajala, Mira; Kilpeläinen, Petri; Viherä-Aarnio, Anneli; Karonen, Maarit; Jyske, Tuula; Marjomäki, Varpu (Frontiers in Microbiology, 2023)
Introduction Recurring viral outbreaks have a significant negative impact on society. This creates a need to develop novel strategies to complement the existing antiviral approaches. There is a need for safe and sustainable antiviral solutions derived from nature. Objective This study aimed to investigate the antiviral potential of willow (Salix spp.) bark hot water extracts against coronaviruses and enteroviruses. Willow bark has long been recognized for its medicinal properties and has been used in traditional medicines. However, its potential as a broad-spectrum antiviral agent remains relatively unexplored. Methods Cytopathic effect inhibition assay and virucidal and qPCR-based assays were used to evaluate the antiviral potential of the bark extracts. The mechanism of action was investigated using time-of-addition assay, confocal microscopy, TEM, thermal, and binding assays. Extracts were fractionated and screened for their chemical composition using high-resolution LC-MS. Results The native Salix samples demonstrated their excellent antiviral potential against the non-enveloped enteroviruses even at room temperature and after 45 s. They were equally effective against the seasonal and pandemic coronaviruses. Confocal microscopy verified the loss of infection capacity by negligible staining of the newly synthesized capsid or spike proteins. Time-of-addition studies demonstrated that Salix bark extract had a direct effect on the virus particles but not through cellular targets. Negative stain TEM and thermal assay showed that antiviral action on enteroviruses was based on the added stability of the virions. In contrast, Salix bark extract caused visible changes in the coronavirus structure, which was demonstrated by the negative stain TEM. However, the binding to the cells was not affected, as verified by the qPCR study. Furthermore, coronavirus accumulated in the cellular endosomes and did not proceed after this stage, based on the confocal studies. None of the tested commercial reference samples, such as salicin, salicylic acid, picein, and triandrin, had any antiviral activity. Fractionation of the extract and subsequent MS analysis revealed that most of the separated fractions were very effective against enteroviruses and contained several different chemical groups such as hydroxycinnamic acid derivatives, flavonoids, and procyanidins. Conclusion Salix spp. bark extracts contain several virucidal agents that are likely to act synergistically and directly on the viruses.